Interaction between Dihydromyricetin and Spike Glycoprotein SARS-COV-2 and its Delta and Omicron variants - a molecular docking study - Oviedo, Anna Karolline Rubim Rodrigues; Oviedo, Vinícius Rodrigues; Fagan, Solange Binotto; Gomes, Patrícia (Disciplinarum Scientia | Naturais e Tecnológicas, 2023)
The SARS-CoV-2 virus has been responsible for a global pandemic which caused millions of deaths. Still, novel antiviral agents have been investigated against SARS-CoV-2. In this view, molecular docking simulations could be used for evaluating possible antiviral agents to be tested in further experimental runs. Hence, the aim of this research was to evaluate the interaction of dihydromyricetin DHM against Spike glycoproteins of pristine SARS-CoV-2 and its Delta and Omicron variants through molecular docking simulations. To validate such results, the same docking protocol was applied to a control structure (galangin, a major component of propolis extract) which was already able to interact with spike glycoprotein of SARS-CoV-2 both in silico and in vitro. Regarding the interaction of DHM/Spike glycoprotein, DHM presented higher spontaneity in binding to Delta (∆G = -8.9 kcal.mol-1) and Omicron (∆G = -7.4 kcal.mol-1) variants than SARS-CoV-2 (∆G = -5.7 kcal.mol-1). Furthermore, DHM/spike glycoprotein interactions for Delta and Omicron variants presented higher similarity to galangin/spike glycoprotein interaction (based on the aminoacid residues involved with the interactions with the polar/non-polar contacts), indicating that DHM and galangin could bind similarly to SARS-CoV-2 variants in the in vitro standpoint. Thus, it is suggested that DHM may be tested as a potential antiviral agent against SARS-CoV-2 through experimental runs.